Hysteresis effects on mechanical behaviour of unsaturated soils - Goh, Shin Guan (2012)
In response to varying climatic conditions, soils above groundwater table and near the ground surface undergo drying and wetting. Under the same stress state, a soil exhibits different water contents and mechanical behaviour when it follows a drying process as opposed to following a wetting process. These differences are referred to as hysteresis of soil. Many research works were conducted on unsaturated soil; however, most of them were limited to soils under drying. The objective of this research is to study the mechanical behaviour of unsaturated soil, particularly the shear strength of soil under hysteresis effects. Twelve published shear strength equations were selected for evaluation using data from literatures. In this study, equations for predicting the unsaturated shear strengths of a soil under drying and wetting were proposed. Series of unsaturated Consolidated Drained (CD) tests were conducted on three different sand-kaolin specimens under multi-cycles of drying and wetting while series of multi-cycled Soil-Water Characteristic Curves (SWCC) tests were conducted on three different sand-kaolin mixtures and three different sands. The CD test results showed that the specimens on the first cycle of drying had a higher shear strength, a higher axial strain at failure and exhibited more ductility, less stiffness, and contractive behaviour during shearing. On the other hand, it was observed that the specimens on the first cycle of wetting had a lower shear strength, a lower axial strain at failure and exhibited less ductility, more stiffness and dilative behaviour during shearing. In addition, the differences between the shear strength characteristics on the drying and wetting paths of the first cycle were found to be more significant than the differences from the drying and wetting paths of the second cycle. The SWCC test results showed that the difference between the drying and wetting SWCCs of the first cycle were larger than those of the subsequent cycles. In addition, the multi-cycled SWCCs of soils were affected by the applied net confining pressure, initial dry density and type of soil significantly. The proposed equations were shown to predict the measured drying and wetting shear strength obtained from this study and the shear strength data from literature successfully in the comparative analyses performed in this study.